Prevalence & Characteristics Of Inguinal Hernia Patients - Indadzi Arsyi Iwan; Berry Erida Hasbi; Hamzakir, Hamzakir (Jurnal EduHealth, 2024)
Based on the World Health Organization (WHO) report, it is stated that between 2005-2010, there were 19,173,279 cases of hernias, and there were 50 million degenerative cases, including hernias, in 2020. The incidence of hernias in developed countries is only 17% per 1000 inhabitants, which is different from what happens in a number of countries on the Asian continent, which reaches 59%.Literature review with narrative review design.A review of 10 pieces of literature showed that inguinal hernia patients mostly suffered from men (95.6%), Spearman's correlation test between age and type of inguinal hernia obtained a p-value = 0.033 (< 0.05) with an average age The highest is 36 -65 years and the lowest is 0-11 years. There is a relationship with the incidence of inguinal hernia with a value of p=0.026, history of chronic cough (68.9%), doing heavy work (82.35%), patients undergoing herniorrhaphy (mesh) surgery. ), Patients with lateral hernia locations dominate cases of hernia recurrence (80%). The time span for most hernia recurrences is <2 years (54%). The prevalence and characteristics of Inguinal Hernia sufferers are mostly men, aged 36-65 years, obesity, history of chronic cough, doing heavy work, undergoing Herniorrhaphy (mesh) surgery with lateral hernia location dominating the majority of hernia recurrences < 2 years.